Epidemiological aspects of dengue in Araçuaí, Middle Jequitinhonha Valley, Minas Gerais (Revista Espinhaço, 2019)
Dengue fever is a febrile infectious disease transmitted by the Aedes aegypti mosquito, which in Brazil represents an epidemic. The objective of this research was to describe the epidemiological aspects of dengue cases reported in the municipality of Araçuaí, Minas Gerais, Brazil, from 2014 to 2018, in a descriptive and quantitative way, with data obtained from the Notification of Injury Information System. The Pearson correlation test was used for analysis between incidence and climatic variables. In the period, 1,138 cases of dengue fever were reported, a predominance of women (62.4%), a prevalent age range of 20 to 49 years (54.6%) and a complete schooling (14.6%). There was a progressive increase in the incidence of dengue in the years 2015 (1,443.92%), 2016 (1,046.84%) and 2017 (352.65%), and decrease in 2018 (108.29%). No correlation was observed between climatic variables and incidence. It is concluded that, after identifying the epidemiological aspects of dengue in Araçuaí, the results indicate the municipality as endemic, characterized as a medium incidence area. The monitoring of the vector by the epidemiological surveillance sector should routinely follow the identification of risk areas for the adoption of disease control and reduction actions in the municipality.
Keywords: Dengue; incidence; epidemiological aspects